Dehydroepiandrosterone upregulates soluble guanylate cyclase and inhibits hypoxic pulmonary hypertension - Oka, Masahiko (2007)
OBJECTIVE: It has been reported that dehydroepiandrosterone is a pulmonary vasodilator and inhibits chronic hypoxia-induced pulmonary hypertension. Additionally, dehydroepiandrosterone has been shown to improve systemic vascular endothelial function. Thus, we hypothesized that chronic treatment with dehydroepiandrosterone would attenuate hypoxic pulmonary hypertension by enhancing pulmonary artery endothelial function. METHODS AND RESULTS: Rats were randomly assigned to five groups. Three groups received food containing 0, 0.3, or 1% dehydroepiandrosterone during a 3-wk-exposure to simulated high altitude (HA). The other 2 groups were kept at Denver’s low altitude (LA) and received food containing 0 or 1% dehydroepiandrosterone. Dehydroepiandrosterone dose-dependently inhibited hypoxic pulmonary hypertension (mean pulmonary artery pressures after treatment with 0, 0.3, and 1% dehydroepiandrosterone = 45 ± 5, 33 ± 2*, and 25 ± 1*# mmHg, respectively. *P<0.05 vs 0% and # vs 0.3%). Dehydroepiandrosterone (1%, 3 wks) treatment started after rats had been exposed to 3-wk hypoxia also effectively reversed established hypoxic pulmonary hypertension. Pulmonary artery rings isolated from both LA and HA rats treated with 1% dehydroepiandrosterone showed enhanced relaxations to acetylcholine and sodium nitroprusside, but not to 8-bromo-cGMP. In the pulmonary artery tissue from dehydroepiandrosterone-treated LA and HA rats, soluble guanylate cyclase, but not endothelial nitric oxide synthase, protein levels were increased. CONCLUSION: These results indicate that the protective effect of dehydroepiandrosterone against hypoxic pulmonary hypertension may involve upregulation of pulmonary artery soluble guanylate cyclase protein expression and augmented pulmonary artery vasodilator responsiveness to nitric oxide.